2019
DOI: 10.3847/1538-4357/ab4426
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Diagnostics of Cool Flare Loops Observed by the SST. I. Inversion of the Ca ii 8542 Å and Hβ Lines

Abstract: Flare loops form an integral part of eruptive events, being detected in the range of temperatures from X-rays down to cool chromospheric-like plasmas. While the hot loops are routinely observed by the Solar Dynamics Observatory's Atmospheric Imaging Assembly (SDO/AIA), cool loops seen off-limb are rare. In this paper we employ unique observations of the SOL2017-09-10T16:06 X8.2-class flare which produced an extended arcade of loops. The Swedish 1-m Solar Telescope (SST) made a series of spectral images of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…This scenario is supported by our observational and modeling results, namely the delayed time of the gradualphase peak of Lyα (t ′ p ) or the plasma cooling time (t cool ) is related to the flare heating magnitude (represented by the impulsive-phase peak flux of Lyα) as well as the flare loop length. In fact, cool flare loops with a chromospheric temperature have been observed in recent years (e.g., Heinzel et al 2018;Koza et al 2019;Heinzel et al 2020). In addition, Milligan et al (2020) reported that the Lyα energy is comparable to, or about an order of magnitude smaller than the total thermal energy.…”
Section: Summary and Interpretationmentioning
confidence: 99%
“…This scenario is supported by our observational and modeling results, namely the delayed time of the gradualphase peak of Lyα (t ′ p ) or the plasma cooling time (t cool ) is related to the flare heating magnitude (represented by the impulsive-phase peak flux of Lyα) as well as the flare loop length. In fact, cool flare loops with a chromospheric temperature have been observed in recent years (e.g., Heinzel et al 2018;Koza et al 2019;Heinzel et al 2020). In addition, Milligan et al (2020) reported that the Lyα energy is comparable to, or about an order of magnitude smaller than the total thermal energy.…”
Section: Summary and Interpretationmentioning
confidence: 99%
“…As such, it can strongly influence the synthetic profiles produced by the models. Moreover, the radiation from the solar disk in the Lyman (Gunár et al 2020) and Mg II h&k (Koza et al 2022) lines changes significantly during the solar cycle. As was shown by Gunár et al (2020), the change in the intensity of the incident radiation in Lyman lines strongly affects not only the intensities of the synthetic Lyman lines but also the Hα line.…”
Section: Incident Radiationmentioning
confidence: 99%
“…A similar approach was also applied by Barczynski et al (2021) to spectra of this tornado-like prominence, but a good fitting was achieved only in areas of low optical thickness of the prominence, mainly in its top and edge parts. For the core of a CME (erupting flux rope), a similar inversion of hydrogen Lyα and Lyβ lines detected by the Ultra-Violet Coronagraph Spectrometer on board the Solar and Heliospheric Observatory was performed by Heinzel et al (2016), while in the case of a loop prominence (flare loops) such a technique was recently applied in Koza et al (2019) who inverted Hβ and Ca II 8542 Å spectral line profiles obtained with SST. Ruan et al (2019) applied an inversion based on a large grid of non-LTE models, but these authors inverted only the characteristic parameters of the Hα line observed by MSDP (integrated line intensity and the FWHM).…”
Section: Introductionmentioning
confidence: 99%
“…The SST data yielded some unique spectropolarimetry which allowed the construction of a map of the magnetic field of the off-limb flare loops (Kuridze et al 2019). Density diagnostics of the bright apex of the flare loop arcade are given by Koza et al (2019). This paper presents an analysis of high-resolution imaging spectroscopy data of off-limb ribbons of the X8.2-class flare acquired by SST.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resolutions were close to the diffraction limit of the telescope at this wavelengths, i.e., ∼0.215 (155 km) and ∼0.122 (88 km) for the selected Ca II and Hβ images in the time series. More details on the observations, data, and radiometric calibration can be found in Kuridze et al (2019) and Koza et al (2019). Due to the highly variable and less-than-optimum seeing, only one CRISP and CHROMIS scan taken at the moment of the best viewing conditions at ∼ 16:32 UT, i.e.…”
Section: Introductionmentioning
confidence: 99%